Biologic and oral disease-modifying antirheumatic drug monotherapy in rheumatoid arthritis. Issue 12 (5th August 2013) - Emery, Paul; Sebba, Anthony; Huizinga, Tom W J
Abstract : Clinical evidence demonstrates coadministration of tumour necrosis factor inhibitor (TNFi) agents and methotrexate (MTX) is more efficacious than administration of TNFi agents alone in patients with rheumatoid arthritis, leading to the perception that coadministration of MTX with all biologic agents or oral disease-modifying antirheumatic drugs is necessary for maximum efficacy. Real-life registry data reveal approximately one-third of patients taking biologic agents use them as monotherapy. Additionally, an analysis of healthcare claims data showed that when MTX was prescribed in conjunction with a biologic agent, as many as 58% of patients did not collect the MTX prescription. Given this discrepancy between perception and real life, we conducted a review of the peer-reviewed literature and rheumatology medical congress abstracts to determine whether data support biologic monotherapy as a treatment option for patients with rheumatoid arthritis. Our analysis suggests only for tocilizumab is there evidence that the efficacy of biologic monotherapy is comparable with combination therapy with MTX.